Functional Outcome after High Tibial Osteotomy for Medial Knee Osteoarthritis - Kanoji, Rajesh Kumar; Himanshu; Suthar, Pradeep Kumar (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
Background: Arthritis is a widespread chronic inflammatory condition affecting millions of individuals worldwide, and among its various manifestations, knee arthritis stands as a substantial burden on both patients and healthcare systems. Knee arthritis, predominantly in the form of osteoarthritis (OA), represents a complex interplay of genetic, mechanical, biochemical, and environmental factors. High tibial osteotomy is a surgical intervention with a growing role in the management of knee arthritis, particularly in patients with malalignment or localized joint disease. Objectives: The aims and objectives of the study are to assess functional outcomes in knee osteoarthritis (OA) cases treated by high tibial osteotomy (HTO) and to study the complications in patients undergoing HTO. Methods: This was a prospective study conducted in the Department of Orthopedics of a tertiary care medical college. 50 patients with moderate-to-severe OA of medial compartment of knee were included in this study. A detailed history with respect to the duration of symptoms and functional disability as manifested by difficulty in climbing stairs, kneeling, or squatting was recorded. All patients underwent HTO. Post-operatively, patients were followed up for 6 months. During follow-up visits, reduction in pain intensity and functional outcome were assessed by visual analog scale (VAS) score and Japanese Orthopedic Association (JOA) Score. Patients were also assessed for complications if any. For statistical purposes, p<0.05 was taken as statistically significant. Results: This study included fifty cases of moderate-to-severe medial compartment knee osteoarthritis (OA) that did not respond to medical management and were treated with high tibial osteotomy (HTO). Out of 50 studied cases, there was a female preponderance with an M: F ratio of 1:1.38. The mean age of affected cases was found to be 62.32±8.94 years. 11 (22.00%) patients were obese (body mass index [BMI] \(\ge\)30) and 32 (64.00%) patients were overweight (BMI \(\ge\)25 but <30). 7 (14.00%) patients had a BMI <25. 38 (76%) patients had severe OA whereas in the remaining 12 (24%) patients, there was moderate OA. There was a significant reduction in pain, as assessed by the VAS score, at the time of final follow-up as compared to the VAS score at the time of presentation (p<0.0001). Similarly, there was a significant functional improvement, as assessed by the JOA score, at the time of final follow-up as compared to the JOA score at the time of presentation (p<0.0001). 7 (14%) patients developed minor complications. All these complications were managed conservatively. Conclusion: No serious surgery-related complication was seen in any of the cases. Patients with moderate to severe OA of medial compartment of knee treated by HTO show excellent outcomes in terms of pain relief and functional outcomes.